Avaliação das condições higienicossanitárias de caldo de cana comercializado por ambulantes no município de Bauru/SP, Brasil (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Evaluation of the sanitaryhygienic conditions of sugarcane juice sold by street vendors in Bauru/SP, Brazil